The group of homomorphisms of abelian torsion groups - M. W. Legg (International Journal of Mathematics and Mathematical Sciences)
Let G and A be abelian torsion groups. In[5], R. S. Pierce develops a complete set of invariants for Hom(G, A). To compute these invariants he introduces, and uses extensively, the group of small homomorphisms of G into A. Also, using some of Pierce's methods, Fuchs characterizes this group in [1]. Our purpose in this paper is to characterize Hom(G, A) in what seems to be a more natural manner than either of the treatments just mentioned.